Implementation of Assessment Techniques at TK Pratama Kids Sukabumi Bandar Lampung - Lina Mauliana; Heny Wulandari; Agus Jatmiko (Journal of Childhood Development, 2021)
Assessment is for collecting, reporting, gathering information about student learning outcomes. In conducting the assessment, there are appropriate techniques for measuring child development. This research is a descriptive qualitative research involving teachers. Data were analyzed qualitatively by collecting data, displaying data and drawing conclusions. The conclusions obtained from several assessment techniques studied were based on a combination of several theories, the results showed that several assessment techniques had been fulfilled, including: the observation assessment technique for children's learning outcomes. however, there are also assessment techniques that are not carried out by teachers on a daily basis, such as the absence of anecdotal notes, children's development scales, and assessment of portfolios. Some of the assessment procedures carried out are formulating or defining activities, preparing assessment tools or techniques, define the assessment criteria, and determine the value. However, there is one procedure that has not been fulfilled, namely collecting data, educators are lacking in collecting data on children's learning outcomes. The principles of assessment in TK Pratama Kids Sukabumi Bandar Lamoung, the teacher have carried out the principles of assessment such as carrying out a thorough, sustainable, oriented, objective, educating and sustainable way. However, there are several principles of assessment that have not been maximized, namely being objective when assessing students.